THE EFFECT OF PSYCHOLOGICAL WELL-BEING ON CAREER ADAPTABILITY MEDIATED EMOTIONAL INTELLIGENCE IN YOGYAKARTA PGSD STUDENTS - Puspa, Adeline Hega (Transpublika Publisher, 2024)
Elementary School (SD) teachers have a psychological workload because their students are still children. These demands must be adapted by elementary school teacher education students in order to be ideal as elementary teachers. The research aimed to determine the effect of psychological well-being on career adaptability mediated by emotional intelligence in early adult students of Elementary School Teacher Education in the Special Region of Yogyakarta. Participants totaled 101 students aged 18-25 years. The research was designed by nonprobability sampling which was analyzed using path analysis. The career adaptability scale used Career Adapt-Abilities Short Form 5 Factor with a validity of 0.716-0.98 with a significance of 0.000-0.001 and a reliability of 0.75-0.93; psychological well-being applied Psychological Well-Being with a validity and reliability of 0.6-0.97 and a significance of 0.000-0.001; and emotional intelligence adapted Emotional Intelligence with a validity of 0.603-0.72 with a significance of 0.000 and a reliability of 0.742-0.9061. The results showed the accumulation of Standardized Coefficients Beta as much as 0.159 with a significance of 0.000-0.001. Meanwhile, the Standardized Coefficients Beta between psychological well-being and career adaptability is only 0.094. Thus, psychological well-being has a significant indirect effect as much as 0.159 on career adaptability through emotional intelligence. Further research suggestions examine the advanced assessments and intervention of psychological well-being effect's on career adaptability through emotional intelligence in college students.